2015
DOI: 10.1021/acs.joc.5b00139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Tetrasaccharide Repeating Unit from Acinetobacter baumannii Serogroup O18 Capitalizing on Phosphorus-Containing Leaving Groups

Abstract: The first convergent synthesis of the tetrasaccharide repeating unit of the polymeric O antigen isolated from Acinetobacter baumannii serogroup O18 has been achieved. The ManNAcβ1→4Gal and GalNAcβ1→3Gal units were successfully obtained through β-selective glycosylation with 2-azido-4,6-O-benzylidene-2-deoxymannosyl diphenyl phosphate and Tf2NH-promoted glycosylation with 2-acetamido-2-deoxygalactosyl diethyl phosphite, respectively. The disaccharide units could be coupled with the aid of TMSClO4 as an activato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…11 Reactions of 4,6-O-benzylidene protected 2-azido-2-deoxymannopyranosyl diphenyl phosphate as well as related phenylthioglycoside donors, however, were reported to proceed in high -selectivity and in good yields. 17,18 Thus, we opted to use a 4,6-O-benzylidene group as a conditions for complete removal. Hence, the mixture was carried through the ensuing introduction of the 4,6-O-benzylidene group using benzaldehyde dimethylacetal and FeCl3 as catalyst 27 to give a mixture of 8 and 9 followed by a subsequent Zemplén transesterification -again with prolonged reaction time -to eventually provide the alcohol 9 in an overall isolated yield of 65% (for 3 steps).…”
Section: Resultsmentioning
confidence: 99%
“…11 Reactions of 4,6-O-benzylidene protected 2-azido-2-deoxymannopyranosyl diphenyl phosphate as well as related phenylthioglycoside donors, however, were reported to proceed in high -selectivity and in good yields. 17,18 Thus, we opted to use a 4,6-O-benzylidene group as a conditions for complete removal. Hence, the mixture was carried through the ensuing introduction of the 4,6-O-benzylidene group using benzaldehyde dimethylacetal and FeCl3 as catalyst 27 to give a mixture of 8 and 9 followed by a subsequent Zemplén transesterification -again with prolonged reaction time -to eventually provide the alcohol 9 in an overall isolated yield of 65% (for 3 steps).…”
Section: Resultsmentioning
confidence: 99%
“…The substrates 13a−h could be accessed in multiple steps from the lactone diol 4. 5b We first investigated the leaving group for the glycosylation and found that diphenyl phosphate 10 was the best leaving group in terms of reactivity and diastereoselectivity (e.g., Table 2, entries 2 vs 1). Next, we evaluated the impact of the TIPSsubstituted group connected to the alkyne.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although great success has been achieved in the chemical synthesis of β-mannosides, stereoselective construction of 2-amino-2-deoxy-β-mannosides is rather underexplored. ,, For instance, stereoselective synthesis of 2-amino-2-deoxy-β-mannosides has been accomplished either through S N 2 inversion of the C2 triflate of β-glucopyranosides by azide anion or involving stereoselective reduction of β-glucopyranosides-derived C2 O -acyloxime . In addition, application of the 4,6- O -benzylidene protecting group, a well-established strategy for construction of β-mannosides, or ( S )-4,6- O -pyruvyl ketal, in the synthesis 2-azido-2-deoxy-β-mannosides afforded poor to moderate anomeric selectivity. Recently, van der Marel, Codee, and co-workers reported that synthesis of 2-azido-2-deoxy-β-mannuronic acid (ManN 3 A) can be achieved with good to excellent anomeric stereoselectivity by using mannosazide methyl uronate donors. , Despite all of the above-mentioned success, it is appealing to develop mild and easily operable approaches for the stereoselective synthesis of β-mannosamines and β-mannosaminuronic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Azido-3-O-benzyl-2-deoxy-6-O-(para-methoxybenzyl)β-D-mannopyranosyl-(1 → 6)-2,3,4-tri-O-benzyl-α-D-glucopyranoside(21). Disaccharide 21 was prepared from lactol donor 11 (41.5 mg, 0.1 mmol) and triflate acceptor 17 (119 mg, 0.2 mmol) following the general procedure.…”
mentioning
confidence: 99%